ANALYSIS OF MUDHARABAH CONTRACTS IN SHARIA BANKING - Vatien Nabila (RADJA PUBLIKA, 2023)
This article aims to analyze Mudharabah contracts in Islamic Banking. Theories related to this article include Mudharabah, Mudharabah Legal Basis, Characteristics, Pillars and Terms, and Distribution of Mudharabah. The method used in this research is a literature study results of this article.